An Earthquake Early Warning System for Southwestern British Columbia - Schlesinger, Angela; Kukovica, Jacob; Rosenberger, Andreas; Heesemann, Martin; Pirenne, Benoît; Robinson, Jessica; Morley, Michael (Frontiers in Earth Science, 2021)
Southwestern British Columbia (BC) is exposed to the highest seismic hazard in Canada. Ocean Networks Canada (ONC) has developed an Earthquake Early Warning (EEW) system for the region. The system successfully utilizes offshore cabled seismic instruments in addition to land-based seismic sensors and integrates displacement data from Global Navigation Satellite Systems (GNSS). The seismic and geodetic data are processed in real-time onsite at 40 different stations along the coast of BC. The processing utilizes P-wave and S-wave detection algorithms for epicentre calculations as well as incorporation of geodetic and seismic displacement data into a Kalman filter to provide magnitude estimates. The system is currently in its commissioning phase and has successfully detected over 60 earthquakes since being deployed in October 2018. To increase the coverage of the EEW system, we are in the process of incorporating detection parameters from neighbouring networks (e.g., the Pacific Northwest Seismic Network (PNSN)) to provide additional information for future event notifications.